MEMBANGUN KESALEHAN SOSIAL MELALUI GERAKAN UPDATE STATUS POSITIF (Kajian Living Quran Terhadap Gerakan Update Status Positif Majelis Alfatihah Kediri Jawa Timur) - Isti'anah, Nur Sholihah Zahro'ul; Rosyidah, Siti Maslikhatu (Al-I'jaz: Jurnal Kewahyuan Islam, 2019)
Today, Indonesia is faced with the threat of national disintegration caused by the misuse of the function of social media. Many circulating posts contain hate speech and hoax news. Based on data released by the Kasatgas Nusantara, Inspector General Gatot Eddy Pramono, from mid-2017 to December 2018, the content of hate speech and hoaxes that were spread on social media penetrated 3,878, both from the original social media accounts; semi anonymous or anonymous. That is a serious problem which can adversely affect on national integration also damage the harmony of life in a society, nation and religion. As an anticipatory step to address this, the members of the Kediri millennial youth who are members of the Alfatihah Assembly, carry out social action in the form of a Positive Status Update Movement. Through this paper, this phenomenon will be examined using the Living Qur'an approach in the framework of a thematic interpretation method. From the results of the study, it was concluded that the movement departs from a motivational understanding of the QS. Ibrahim verses 24-26. In the verse it is explained that the thayyibah (good expression) is described as a good tree: its roots are sturdy, its branches soar up to the sky and its fruit can benefit anyone around it. The application, each member of the assembly carries out a tradition of positive status updates through their respective social media accounts, the content can be in the form of prayer, scientific studies, inspirational stories, ulama's advice, wisdom lessons, and motivation. The movement is an effort to narrow the space, or at least be a counterweight to the spread of negative content, so as to create a safe, peaceful and comfortable atmosphere to build a peaceful and prosperous country in the grace of Almighty God.Keyword: Living Qur'an, Positive Status Updates, social piety